Combined parenchymal and vascular imaging: High spatiotemporal resolution arterial evaluation of hepatocellular carcinoma. Issue 4 (4th September 2015) - Hope, Thomas A.; Petkovska, Iva; Saranathan, Manojkumar; Hargreaves, Brian A.; Vasanawala, Shreyas S.
Abstract : Purpose: To assess the ability of high‐resolution arterial phase imaging of hepatocellular carcinoma (HCC) to provide combined vascular characterization and parenchymal evaluation. Materials and Methods: Thirty‐eight consecutive studies in cirrhotic patients with HCC scanned with a view‐shared 2‐point‐Dixon‐based Differential Subsampling with Cartesian Ordering (DISCO) sequence were analyzed. Lesion contrast relative to precontrast and adjacent parenchyma was evaluated and compared using a Fisher's exact test. Visibility of hepatic arteries and tumor feeding vessels were graded on a 5‐point scale. Catheter angiography was used as a reference standard for arterial anatomy. Results: The high spatiotemporal multiphasic acquisition allowed imaging of both the angiographic and late arterial phase in 30 of 38 studies with good image quality. Maximal lesion enhancement compared to precontrast occurred more frequently during the late arterial phase compared to maximal lesion‐to‐adjacent, which occurred more frequently during the early arterial phase ( P  < 0.001). Common and proper hepatic arteries were visualized adequately in 100%, right hepatic artery in 94–97%, left hepatic artery in 94%, and segmental vessel in 83% of cases. Arterial variants were detected with sensitivity of 87–100% and specificity of 100%. Conclusion: High spatiotemporal resolution arterial phase imaging provides multiple angiographic and arterial phases in a single breath‐hold, enabling accurate depiction of vascular anatomy while maintain optimal arterial phase imaging for characterization of focal lesions. J. Magn. Reson. Imaging 2016;43:859–865